Effects of peripheral and different inspiratory muscle training methods in coronary artery disease patients with metabolic syndrome: A randomized-controlled trial - Muammer, Kıymet; Mutluay, Fatma; Demir, Rengin; Arat Özkan, Alev (W.B. Saunders Co Ltd, 2020)
Objective: To investigate the effects of peripheral muscle training (PMT) and different inspiratory muscle training (IMT) methods on respiratory functions, exercise capacity, and biochemistry parameters in coronary artery disease patients with metabolic syndrome.Methods: This prospective, single-blind, randomized-controlled study included 60 patients of stable coronary artery disease with metabolic syndrome (New York Heart Association [NYHA] Class I-II, left ventricular ejection fraction >40%). Patients were randomly divided into three groups: neuromuscular electrical stimulation (NMES) plus PMT group (NMES + PMT group, n = 20), IMT plus PMT group (IMT + PMT group, n = 20) and PMT group (PMT group, n = 20). Treatment continued for six weeks for all groups. The NMES was applied to rectus abdominis, IMT was applied with 30% of maximal inspiratory pressures, and PMT was applied at home. Spirometry, maximal inspiratory and expiratory pressure, dyspnea scores, exercise stress test, and biochemistry parameters were measured before and after training.Results: There were significant improvements in spirometric tests, respiratory muscle strength, dyspnea scores, exercise capacity, fasting blood glucose, and antistreptolysin O after treatment in all groups (p < 0.05). Significant improvements in C-reactive protein and erythrocyte sedimentation rate were observed in NMES + PMT and IMT + PMT groups (p < 0.05). Among the groups, there was a significant difference in maximal inspiratory pressure (p = 0.02) and erythrocyte sedimentation rate (p = 0.037) in favor of NMES + PMT group (p < 0.05).Conclusion: Our study results showed significant improvements in respiratory functions, exercise capacity, and biochemistry markers in all groups. Different IMT methods can be used in cardiopulmonary rehabilitation to improve exercise intolerance in coronary artery disease patients with metabolic syndrome.
Keywords: Coronary Artery Disease; Metabolic Syndrome; Neuromuscular Electrical Stimulation; Inspiratory Muscle Training; Peripheral Muscle Training